Transnational Disorders: Returned Migrants at Oaxaca's Psychiatric Hospital. (8th October 2014) - Duncan, Whitney L.
Abstract : This article examines experiences of returned migrants seeking mental health care at the public psychiatric hospital in Oaxaca, Mexico. Approximately one‐third of the hospital's patients have migration experience, and many return to Oaxaca due to mental health crises precipitated by conditions of structural vulnerability and "illegality" in the United States. Once home, migrants, their families, and their doctors struggle to interpret and allay these "transnational disorders"—disorders structurally produced and personally experienced within the borders of more than one country. Considering how space and time shape illness and treatment among transnational migrants, I contend that a critical phenomenology of illegality must incorporate migrant experience and political economy on both sides of the border before, during, and after migration.